Scolarité, soins et religion : enjeux éducatifs autour de l'enfant séropositif dans une institution catholique en Inde du Sud - Marion Delpeu (Les éditions de la Maison des sciences de l'Homme, 2019)
Medical developments in HIV (treatment, testing) during the 2000s have significantly changed the institutional care plans for HIV-positive children in India. A Catholic reception centre for HIV-positive adults and children - initially a refuge for AIDS patients - transformed its structure to prepare a future for Hindu, poor and low-caste children, sometimes orphans. Based on the ethnography of this centre, born from the meeting between two Catholic congregations (Indian compassionate nuns and Western Brothers with a traditionalist tendency), this article examines the implementation of an educational project that combines religion, education and care. We analyze how this project generates daily tensions between Western missionaries and Indian nuns. We then present the practices of resistance, adaptation and acceptance of adolescents who express themselves in a context of uncertainty and physical fragility.